Norms for 70 semantic categories from Rioplatense Spanish-speaking adolescents - Martínez Cuitiño, Macarena; Zamora, Dolores Jazmín; Camilotto, Natalia Rocío; Romero, Nicolás Nahuel; Shalóm, Diego (Revista de Investigación en Logopedia, 2024)
The large number of semantic category norms published in recent decades is explained by the need to have norms for each culture and linguistic variety. These are elaborated from extensive corpora of category exemplars that are obtained by means of a semantic fluency task. The number and variety of such exemplars are influenced by other sociodemographic variables such as culture, sex, and age. Although category norms are available for adults and children, up to now there are no category norms for the adolescent population. This study presents the first norms for 70 semantic categories, which were collected from a sample of 480 Argentine adolescents. The most frequent exemplars, the frequency of appearance of each one, and the number of times they are activated in the first position are provided in a database presented both globally by category and dissociated by biological sex.
Keywords: category norms; semantic categories; adolescents; semantic fluency; Spanish